Mechanisms and Implications of Dual-Acting Methotrexate in Folate-Targeted Nanotherapeutic Delivery - Wong, Pamela; Choi, Seok (International journal of molecular sciences, 2015)
The rational design of a nanoplatform in drug delivery plays a crucial role in determining its targeting specificity and efficacy in vivo. A conventional approach relies on the surface conjugation of a nanometer-sized particle with two functionally distinct types of molecules, one as a targeting ligand, and the other as a therapeutic agent to be delivered to the diseased cell. However, an alternative simplified approach can be used, in which a single type of molecule displaying dual function as both a targeting ligand and therapeutic agent is conjugated to the nanoparticle. In this review, we evaluate the validity of this new strategy by using methotrexate, which displays multifunctional mechanisms of action. Methotrexate binds to the folate receptor, a surface biomarker frequently overexpressed in tumor cells, and also inhibits dihydrofolate reductase, an enzyme critical for cell survival and division. Thus we describe a series of fifth generation poly(amido amine) dendrimers conjugated with methotrexate, and discuss several lines of evidence supporting the efficacy of this new platform strategy based on surface plasmon resonance spectroscopy, enzyme activity assays, and cell-based studies with folate receptor (+) KB cancer cells.